Fisheries ecological knowledge, FEK: Contribution to the knowledge of the ecology and distribution of houndsharks and dogfish shark (family Triakidae and Squalidae) in the Canary Islands - Rosario Luque Cabrera; Ana Espino-Ruano; José Juan Castro; Airam Guerra-Marrero; Lorena Couce-Montero; Raibel Núñez-González; Tomàs Bañeras; David Jiménez-Alvarado (PLoS ONE, 2026)
Currently, it is assumed that most of elasmobranchs (sharks, rays and skates) had suffered a high depletion in their populations worldwide, but there is an important lack of biological and fishing information over the bulk of the species that do not permit to determine the real status of their populations. Seven of these scarce information species are the houndsharks and dogfish shark (family Triakidae and Squalidae) found in the Canary Islands, which actual status level and contribution to the catch in the archipelago are still unknown. 136 interviews were carried out among artisanal fishers from all the islands, in which very few of them were able to distinguish all the species. Two houndshark and one dogfish shark species were frequently identified and/or caught (the common smoothhound ( Mustelus mustelus ), the tope shark ( Galeorhinus galeus ) , and the shortnose spurdog ( Squalus megalops )), and half of the fishers were not able to distinguish the sex of these fishes. The houndsharks and dogfish shark are preferentially distributed down to 200 metres depth, with higher catches off the eastern and central islands. These sharks are caught all year round with highest peaks during the summer months, probably coinciding with aggregations for mating and reproduction in shallower waters. Houndsharks and dogfish shark are generally not targeted by artisanal fisheries and, although sometimes landed, most of the catch is usually discarded. Sharks caught range from 100 to 120 cm in total length for common smoothhound and tope sharks, while the catch size for shortnose spurdog varies between 50 and 60 cm in total length. Improving taxonomic knowledge within the fishing sector is essential for sustainable management and conservation of houndshark and dogfish shark species in Canarian waters.